2017
DOI: 10.1038/gim.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of genomic sequencing for population screening of immunodeficiencies in the newborn

Abstract: PurposeImmunodeficiency screening has been added to many state-directed newborn screening programs. The current methodology is limited to screening for severe T-cell lymphopenia disorders. We evaluated the potential of genomic sequencing to augment current newborn screening for immunodeficiency, including identification of non-T cell disorders.MethodsWe analyzed whole-genome sequencing (WGS) and clinical data from a cohort of 1,349 newborn-parent trios by genotype-first and phenotype-first approaches. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Three of these children had pathogenic mutations in other (non-PID) genes which correlated clinically. No additional causative variants were found in the other children, the majority of whom were considered to be unlikely to have a PID [32]. These findings are consistent with results of a survey conducted by Boyle et al, who determined a PID prevalence of 1 in 1200 in the US [33].…”
Section: The Future: the Role Of Next-generation Sequencing In Newborsupporting
confidence: 90%
See 2 more Smart Citations
“…Three of these children had pathogenic mutations in other (non-PID) genes which correlated clinically. No additional causative variants were found in the other children, the majority of whom were considered to be unlikely to have a PID [32]. These findings are consistent with results of a survey conducted by Boyle et al, who determined a PID prevalence of 1 in 1200 in the US [33].…”
Section: The Future: the Role Of Next-generation Sequencing In Newborsupporting
confidence: 90%
“…Pavey et al recently reported the results of WGS-based screening for PID in a cohort of 1349 newborn and parent trios, who were analyzed for variants in 329 known immunodeficiency genes [32]. A genotype-first pipeline resulted in identification of 396 newborns with pathogenic/likely pathogenic mutations, however on further analysis, only one individual was found to have a genomically predicted immunodeficiency (complement component C9 deficiency).…”
Section: The Future: the Role Of Next-generation Sequencing In Newbormentioning
confidence: 99%
See 1 more Smart Citation
“…For conditions like cystic fibrosis and lysosomal storage disorders, sequencing can help to confirm a diagnosis and can provide additional prognostic information . For nonspecific disorders, such as immunodeficiencies and hearing loss, gene panels or whole‐exome sequencing can help determine the underlying cause of the condition, information that is critical for appropriate medical management, surveillance, and treatment . In the future, widespread use of sequencing as a diagnostic follow‐up to existing screening tests could also decrease the number of false positives generated in public health programs, thereby lessening the emotional and financial burden on parents and the health care system.…”
Section: Essaymentioning
confidence: 99%
“…4 For nonspecific disorders, such as immunodeficiencies and hearing loss, gene panels or whole-exome sequencing can help determine the underlying cause of the condition, information that is critical for appropriate medical management, surveillance, and treatment. 5 In the future, widespread use of sequencing as a diagnostic follow-up to existing screening tests could also decrease the number of false positives generated in public health programs, thereby lessening the emotional and financial burden on parents and the health care system. As one example, elevated phenylalanine levels detected using today's main newborn screening technology (tandem mass spectrometry) are associated with phenylketonuria (PKU) disease, the disorder that drove the establishment of newborn screening programs worldwide.…”
mentioning
confidence: 99%